Neotype designation for Plangia graminea (Serville, 1838) and two new Plangia species from Tanzania, East Africa (Orthoptera: Tettigoniidae: Phaneropterinae) - Hemp, Claudia (Zootaxa, 2017)
A neotype is assigned for Plangia graminea (Serville) since the holotype is lost. Two new Plangia species, P. amaniensis n. sp. from the East Usambara Mountains and P. variacantans n. sp. from the Uluguru Mountains of Tanzania are newly described.